2021
DOI: 10.1002/bbb.2261
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of lignin‐containing cellulose nanocrystals: life‐cycle environmental impacts and opportunities for improvement

Abstract: Deep eutectic solvent (DES) has recently been attracting great interest for its role in isolating nanocellulose owing to its distinct advantages of biodegradability, low toxicity, and recyclability. Lignin‐containing cellulose nanocrystals (LCNCs) obtained using DES pretreatment has led to an improvement in the production of nanomaterials. Understanding the potential environmental impacts of this novel technology at the laboratory scale provides important insights to improve its sustainability at full scale in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Panić et al (2021) showed that when using betaine or thymol as HBA, and ethylene glycol, glucose, sucrose, or decanoic acid as the HBD, the extracts possessed desirable activity toward the growth of normal human keratinocytes. At the moment, there is no denying that some DESs are also slightly toxic (Zargar et al 2022), but they are still much less toxic than some ionic liquids (Musarurwa and Tavengwa 2021). More importantly, there is also less information available to give a conclusion, which means that further study is necessary.…”
Section: The Toxicity Of Dessmentioning
confidence: 99%
“…Panić et al (2021) showed that when using betaine or thymol as HBA, and ethylene glycol, glucose, sucrose, or decanoic acid as the HBD, the extracts possessed desirable activity toward the growth of normal human keratinocytes. At the moment, there is no denying that some DESs are also slightly toxic (Zargar et al 2022), but they are still much less toxic than some ionic liquids (Musarurwa and Tavengwa 2021). More importantly, there is also less information available to give a conclusion, which means that further study is necessary.…”
Section: The Toxicity Of Dessmentioning
confidence: 99%
“…DES-treated lignin-containing CNCs contribute to the improvement of nanomaterial production. Zargar et al (2022) pointed to the environmental impact of the production of lignin-containing CNCs from thermomechanical pulp after the application of acidic DES based on several analyses. Furthermore, the effect on the production of lignin-containing CNCs depending on the DES chemical composition, dose, and reuse was studied selecting three factors: DES components (choline chloride, oxalic acid dihydrate, p-toluenesulfonic acid), temperature (80-90 °C), and hydrolysis time (3-6 h).…”
Section: Production Of Lignin-containing Cellulose Nanofibrils/cellul...mentioning
confidence: 99%
“…For CNCs, energy demand was reported to significantly affect the overall impacts, greenhouse gas (GHG) emissions, in particular. Energy demands of CNCs production from different feedstocks and production routes varied from 457 to 15,943 MJ, and corresponding global warming potential (GWP) ranged from 12.9 to 1,086 kg CO 2 eq./kg CNC (Zargar et al, 2021). De Figueirêdo et al (2012 employed acid hydrolysis of two different feedstocks i.e., cotton fibers and coconut fibers for CNC production.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…For CNFs, energy demands in the literature ranged from 87 to 19,000 MJ, and the GWP was reported to be between 0.79 and 800 kg CO 2 eq./kg CNF (Zargar et al, 2021). High energy demands of CNF production from mechanical treatments pose a major concern, even though these methods are suitable for scaling.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
See 1 more Smart Citation